Sociological perspectives on sport the games outside the games - Karen, David; Washington, Robert E. 1941- (London Routledge, Taylor & Francis, 2015)
Sociological Perspectives on Sport: The Games Outside the Games seeks not only to inform students about the sports world but also to offer them analytical skills and the application of theoretical perspectives that deepen their awareness and understanding of social processes linking sports to the larger social world. With six original framing essays linking sport to a variety of topics, including race, class, gender, media, politics, deviance, and globalization, and 37 reprinted articles, this text/reader sets a new standard for excellence in teaching sports and society.
Section 4: The political economy and the politics of sports: dynamics and diffusion -- Cuban baseball: ideology, politics, and market forces Katherine E. Baird -- Public dollars, private stafiums, and democracy Kevin J. Delaney and Rick Eckstein -- Sport, masculinity, and black cultural resistance Ben Carrington -- Gay games or gay olympics? Implications for lesbian inclusion Helen Jefferson Lenskyj -- Argentina's left-wingers Leslie Ray -- Hoosier Whiteness and the Indiana Pacers: racialized strategic change and he politics of organizational sensemaking R. Scott Carey -- Where are the jocks for justice? Kelly Candaele and Peter Dreier -- Section 5: Breaking the normative rules: the problems of deviance in sports -- Creating the Frankenstein athlete: the drug culture in sports Fran Zimniuch -- Discourses of deception: cheating in professional running Peter G. Mewett -- Male athletes, injuries, and violence Michael A. Messner -- The Sprewell/Carlesimo episode: unacceptable violence or unacceptable victim? Theresa Walton -- Unnecessary roughness? school sports, peer networks, and male adolescent violence Derek A. Kraeger -- The dark side of social capital: an ethnography of sport governance Dino Numerato and Simone Baglioni -- Women athletes as falsely accused deviants: managing the lesbian stigma Elaine M. Blinde and Diane E. Taub -- Section 6: Globalization and sports -- Theorizing sport in the global process joseph Maguire -- The denationalization of sport: de-ethnicization of the nation and identity de-territorialization Raffaele Poli -- The global and the local in our contemporary sports cultures Andrei S. Markovits -- Between adoption and resistance: grobalization and glovalization in he development of Israeli basketball Eran Shor and Yair Galily -- What happens while the official looks the other way?: citizenship, transnational spors migrants and the circumvention of the state Thomas F. Carter.
Includes bibliographical references and index.
Keywords: Sports -- Sociological aspects